Modeling water resources management at the basin level: methodology and application to the Maipo River Basin - Cai, Ximing; Ringler, Claudia; Rosegrant, Mark W. (International Food Policy Research Institute, 2006)
With increasing competition for water across sectors and regions, the river basin has been recognized as the appropriate unit of analysis for addressing the challenges of water resources management. Modeling at this scale can provide essential information for policymakers in their resource allocation decisions. A river basin system is made up of water source components, instream and off-stream demand components, and intermediate (treatment and recycling) components. The river basin is thus characterized by natural and physical processes but also by human-made projects and management policies. The essential relations within each component and the interrelations among these components in the basin can be represented in an integrated modeling framework. Integrated hydrologic and economic models are well equipped to assess water management and policy issues in a river basin setting. McKinney et al. (1999) reviewed state-of-the-art modeling approaches to integrated water resources management at the river basin scale... This report presents the methodology development of an integrated economic–hydrologic river-basin model, as well as the application of this prototype to the Maipo River Basin in Chile. The model is based on a node-link river-basin network, including multiple source nodes (reservoirs, aquifers, river reaches, and so on) and demand sites, for municipal and industrial (M&I), hydropower, and agricultural water demands.